The relationship between gross motor skills and visual perception of preschoolers - Kezban Tepelı (Türk Spor ve Egzersiz Dergisi)
Answers were searched for these questions; “Is there a relationship between visual perceptions and gross motor skills of preschool children?”, “Are preschool children's visual perceptions predictors of their gross motor skills?”, “Is there any difference between visual perceptions of the children having low, average and high level of gross motor skills?” within this study where the relationship between preschool children's visual perceptions and their gross motor skills were comparatively examined. 322 children, ages ranging from 54 to 59 months, participated in this research designed in relational screening model. 52% of the children are boys, 48% of them are girls. As a data collection tool; Frostig Developmental Test of Visual Perception (FDTVP), developed by Frostig was used together with Test of Gross Motor Development-2 (TGMD-2), developed by Ulrich and Tepeli et al. adapted to Turkish. “Pearson Product Moment Correlation Coefficient”, “Multiple Linear Regression” and “One-Way ANOVA” statistical methods were used in data analysis. Very high directly proportional relationships were determined between children's TGMD-2 sub test and total test scores and their FDTVP sub test and total test scores (p lt;0.01). FDTVP sub tests were determined to explain 27% of the total variance in Locomotor Skills sub test, 70% of the total variance in Object Control Skills sub test, and 60% of the total variance in Gross Motor Skills total test of TGMD-2. In addition, it was determined that FDTVP sub test and total test scores of the children differs significantly according to their gross motor skills.